Identification of Antioxidant Compounds using the DPPH Radical Scavenging Method from Ethanol and Methanol Extracts of the Leaves and Fruits of the Renggak Plant (Ammomum dealbatum R.) - Rahmawati Rahmawati; Meliana Meliana; Lestia Furnapasta; Syarifa Wahidah Al Idrus; Baiq Fara Dwirani Sofia; Sya’ban Putra Adiguna; Jono Irawan (UNIVERSITAS SEBELAS MARET (UNS), 2026)
This study aims to screen antioxidant compounds from the renggak plant (Amomum dealbatum R.). Screening of phytochemicals was carried out on the leaves and peel of the renggak fruit by the extraction method using ethanol and methanol solvents. Extraction was carried out by maceration, and the antioxidant potential test was carried out by measuring the extract's scavenging activity against DPPH radicals. In the fruit peel, both ethanol and methanol extracts tested positive for all phytochemicals, while in the leaves, ethanol extract was positive only for tannins and alkaloids, and methanol extract for flavonoids, saponins, tannins, and alkaloids. The difference in results was caused by differences in solvent polarity. The results of the antioxidant test showed that the leaf extract had an IC₅₀ value of 44.31 µM, while the fruit peel extract had an IC₅₀ value of 144.57 µM. The lower IC₅₀ value in the leaf extract indicates that the bioactive compounds contained therein have higher antioxidant potential than the fruit peel, as they can inhibit 50% of free radical activity at lower concentrations. The results of this study provide additional phytochemical and antioxidant sources from plant sources, for use as raw materials in the pharmaceutical and cosmetic industries.